Speech Therapy and Mental Health: Service Group to Institutionalized Individuals with Mental Disorders - Paiva Bueno de Almeida, Beatriz; Cunha, Maria Claudia; de Paula Souza, Luiz Augusto (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2015)
The objective of this article is to analyze the speech developed at the CAIS-SR, an institution whose history was marked by the process of institutionalization of mental patients. The research method combines survey of speech-language record of the activities carried out, which occurred between 2001 and 2006, interviews with professional teams of CAIS-SR and group patients “Sabiá na Laranjeira” and analysis of the group work done with patients. Presented key issues to care of patients with mental disorders: the marks that isolation makes the life history of these subjects, the composition and relevance of inter-and multidisciplinary teams in mental health; social exclusion and the search for activities that help in building a new and more satisfactory social conditions for such subjects. The speech therapist should value and encourage communication and discursive circulation among patients and those with family members and shedding light on the importance of communication.